Species richness of cuckoo bumblebees is determined by the geographical range area of the host bumblebee. Issue 6 (2nd September 2016) - Suhonen, Jukka; Rannikko, Janina; Sorvari, Jouni
Abstract: The geographical range area of host hypothesis predicts that regionally widespread host species are able to support higher local parasite species richness. In this study, we investigated the macro‐ecological patterns in cuckoo bumblebee species richness in relation to the geographical range area of their bumblebee hosts (Hymenoptera: Apidae: Bombini). The cuckoo bumblebees live in naturally fragmented environments composed of host bumblebee colonies upon which they are exclusively dependent. We collected data on all 11 known cuckoo bumblebee species that are classified as parasites (obligate workerless social parasites) – and all 69 known bumblebee species in Europe. Whereas some bumblebee hosts harbour several cuckoo bumblebee species, most are cuckoo free (78%). Bumblebees with a large geographical range area hosted more cuckoo bumblebee species than host species with a narrow range area. The geographical range area of cuckoo bumblebee species increased with increasing combined range area of all hosts, but it was smaller than combined range area of all hosts. We found support for the hypothesis that the geographical range area of the host bumblebee species has an effect on the species richness of cuckoo bumblebees. If the range area of the host bumblebee species decreases, cuckoo bumblebees may become vulnerable to extinction.